The Effect of Augmented Reality Media on Mathematics Learning Outcomes of Elementary School Students - Lintiasri, Suci; Nisa, Ana Fitrotun; Masjid, Akbar Al; Cahyani, Berliana Henu (FKIP Universitas Lampung, 2024)
This study aims to test the effect of Augmented Reality (AR) media on mathematics learning outcomes of fifth-grade students at SD Negeri 2 Tibayan, Klaten Regency. The use of Augmenter Reality Media can serve as an alternative in innovative learning activities. The study used pre-experimental research methods, one group pretest, and a posttest design using learning outcomes through pretest and posttest to determine the effect of before and after using Augmented Reality media. The subjects of this study were students of fifth grade SD Negeri 2 Tibayan, totaling 20 students, with 12 male students and 8 female students. This study uses instruments in the form of learning outcomes tests and learning devices in the form of teaching modules. Data analysis techniques in this study are descriptive and infersional analysis techniques. The results of the study before using Augmented Reality (AR) media showed a low level of understanding of the concept, with an average value of 64. After using Augmented Reality (AR) Media obtained an average of 80,450 with a standard deviation of 10,679, as well as the lowest value of 65 and the highest of 100 so that it shows the level of understanding of the concept in the high category. Based on these results, it can be concluded that Augmented Reality (AR) media has a significant influence on students ' math learning outcomes. Keywords: augmented reality, mathematics learning outcomes.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp2000-2012